Gọi d là ƯCLN của 2n+3 và 2n2+4n+1,\(d\in N\ne0\)
\(\Rightarrow\hept{\begin{cases}2n+3⋮d\left(1\right)\\2n^2+4n+1⋮d\left(2\right)\end{cases}\Rightarrow\hept{\begin{cases}\left(2n+3\right)^2⋮d\\2\left(2n^2+4n+1\right)⋮d\end{cases}}}\Rightarrow\hept{\begin{cases}4n^2+12n+9⋮d\\4n^2+8n+2⋮d\end{cases}}\)
\(\Rightarrow4n^2+12n+9-4n^2-8n-2⋮d\)
\(\Rightarrow4n+7⋮d\left(1\right)\)
Từ\(2n+3⋮d\)\(\Rightarrow2\left(2n+3\right)⋮d\Rightarrow4n+6⋮d\left(2\right)\)
Từ (1) và (2) \(\Rightarrow4n+7-4n-6⋮d\Rightarrow1⋮d\Rightarrow d=1\)
Vậy...
Đúng 0
Bình luận (0)